COVID-19 Awareness Among Dental Professionals in Indonesia - Widyarman, Armelia Sari; Bachtiar, Endang W.; Theodorea, Citra Fragrantia; Rizal, M. Ihsan; Roeslan, M. Orliando; Djamil, Melanie S.; Santosa, Didi N.; Bachtiar, Boy M. (Frontiers in Medicine, 2020)
Background:The COVID-19 pandemic caused by SARS-CoV-2 has claimed thousands of lives worldwide. To enhance knowledge and awareness of COVID-19, considerable online resources have been made available, including aspects related to the dental profession. The study aim was to examine the knowledge, perception and attitude of dental professionals in Indonesia toward COVID-19. We conducted a survey via a questionnaire created using Google docs and distributed to 632 members of the Indonesian Dental Association in the context of a webinar hosted by the Indonesian Oral Biology Association on first June,2020. Materials and methods:The questionnaire consisted of 17 items pertaining to demographic data, knowledge and virus identification, awareness regarding drugs commonly used in dentistry during pandemic and research opportunities. Participants were asked to complete the questionnaire after the webinar by choosing one answer to each question. For the analysis, participants were divided into three groups according to their professional background i.e. employment at national hospital, private hospital, or academic faculty. Data were analyzed using descriptive statistics and expressed as frequencies and percentages. The chi-square test was used to investigate the association between professional activity and the level of knowledge, perceptions and attitudes about COVID-19. Results:Sixty percent of the participants correctly identified the pathogenesis of the disease. This knowledge was not associated with their professional affiliation (p=0.95). 67% had comprehensive knowledge about virus detection methods. This knowledge was not associated with their affiliation either (p=0.54). Questions regarding drugs of choice, prevention, and the spread of COVID-19 were correctly answered by 89%, 96%, and 82% of the participants, respectively. Knowledge of these aspects were significantly associated with the professional affiliation (p<0.05). All respondents were optimistic regarding research opportunities (p<0.01). Respondents from academics were more interested in joining COVID-19-related research projects with governmental institutions (p<0.01). Conclusion:Knowledge and awareness of COVID-19 among Indonesian dentists are reasonably good. However, further improvement would be beneficial to manage patients during this pandemic. As the number of COVID-19 cases continue to rise in Indonesia, it is important that dentists keep abreast of the updated knowledge on this moving field. Dentist knowledge on infection control should be strengthened through continuous educational programs.